Charge Dynamics in Organic Semiconductors : From Chemical Structures to Devices - Kordt, Pascal (Berlin ; Boston : De Gruyter, 2016)
In the field of organic semiconductors researchers and manufacturers are faced with a wide range of potential molecules. This work presents concepts for simulation-based predictions of material characteristics starting from chemical stuctures. The focus lies on charge transport - be it in microscopic models of amorphous morphologies, lattice models or large-scale device models.An extensive introductory review, which also includes experimental techniques, makes this work interesting for a broad readership. Contents: Organic Semiconductor DevicesExperimental TechniquesCharge Dynamics at Dierent ScalesComputational MethodsEnergetics and Dispersive TransportCorrelated Energetic LandscapesMicroscopic, Stochastic and Device SimulationsParametrization of Lattice ModelsDrift-Diusion with Microscopic Link
Frontmatter -- Acknowledgements -- Abstract -- Contents -- Introduction -- 1. Organic Semiconductor Devices -- 2. Experimental Techniques -- 3. Charge Dynamics at Different Scales -- 4. Computational Methods -- 5. Energetics and Dispersive Transport -- 6. Correlated Energetic Landscapes -- 7. Microscopic, Stochastic and Device Simulations -- 8. Parametrization of Lattice Models -- 9. Drift-Diffusion with Microscopic Link -- Conclusions and Outlook -- A. Molecule Abbreviations -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mrz 2019)
Keywords: Charge density; Charge dynamics; Charge transport; Device simulations; Organic light emitting diodes; 2 -- isacsh